Contemporary strategy analysis - Grant, Robert M., 1948- (John Wiley & Sons, 2019)
Now in its tenth edition, Contemporary Strategy Analysis continues its tradition of accessibility, practicality, and real-world relevance to graduate and undergraduate students around the world. Focusing on strategic analysis, value creation, and implementation, this book provides a rigorous grounding in essential principles while offering up-to-date perspectives based on practices used at leading companies across industries and borders. Comprehensive coverage merges theory and application through new and updated cases, and the discussion surrounding business policy, business strategy, and the business environment links concept to context for a holistic understanding of the mechanisms at work. To keep pace with the fields constant evolution, this new edition has been revised to reflect the current business landscape with expanded coverage of critical topics including disruption, innovation, technology, and other factors impacting strategic planning and implementation. Global perspectives throughout highlight the dynamic nature of strategic management in the face of borderless business, equipping students with the well-rounded knowledge base the future of business demands.